Pengelolaan Media Pembelajaran Di Sekolah Dasar Negeri 3 Boyolali - Siswanto, Siswanto; , Prof.Dr.Ngalim Abdul, MM, M.Hum; , Dr.Suyatmini,SE.,M.Si (2016)
ABSTRACT Siswanto. Q 100 140 005 Media Management Learning at SDN 3 Boyolali. Thesis. Surakarta Muhammadiyah University Graduate Program. 2016. Instructional media has an important role in the learning process. Nevertheless, many schools lack an understanding of the importance of learning media in support of learning in the classroom. Learning media has not been seen as an important factor in the learning process. The pattern of planning, procurement, organization and control of teaching media in SDN 3 Boyolali can be used as a reference by other schools. Learning media can be used by teachers to take turns so that classroom learning does not saturate. Diverse array of media types of learning, encourages the management and organization of the learning media. This is the basis of the author examines the media management model of learning in SDN 3 Boyolali. This study has three objectives. 1. Describe the planning of instructional media in SDN 3 Boyolali. 2. Describe the use of instructional media in SDN 3 Boyolali. 3. Describe the maintenance of instructional media in SDN 3 Boyolali. The research is a qualitative research design with phenomenology. Implementation of research at SDN 3 Boyolali. Sources in the research is the principal and teachers at SDN 3 Boyolali.Teknik data collection is interview, observation and documentation. Analysis of data using an interactive model. This study has three outcomes. 1. Planning the learning media is an inventory of types of instructional media, merelevansikan media teaching materials crate globe use in social studies, confirming media with other teachers or friends of the group, preparing a book support package from the government, and pour the planned use of media in learning devices , 2. The use of instructional media is able to show a medium of learning makes the students more easily understand the teaching materials, instructional media were able to show increasing curiosity about the new sciences, capable of showing the learning media help teachers explain the learning material, and be able to demonstrate learning media reduces verbal learning theory. 3. Maintenance of instructional media is keeping the medium of learning material or objects in special cabinets, learning media in the form of a file stored on the computer, and the media is damaged beyond repair maintenance direct teachers or experts. Keywords: management, media, learning